Human B1 Cell Frequency: Isolation and Analysis of Human B1 Cells - Griffin, Daniel; Rothstein, Thomas L. (Frontiers in Immunology, 2012)
Controversy over the frequency of human B1 cells in normal individuals has arisen as different labs have begun to employ non-uniform techniques to study this population. The phenotypic profile and relative paucity of circulating human B1 cells place constraints on methodology to identify and isolate this population. Multiple steps must be optimized to insure accurate enumeration and optimal purification. In the course of working with human B1 cells we have developed a successful strategy that provides consistent analysis of B1 cells for frequency determination and efficient isolation of B1 cells for functional studies. Here we discuss issues attendant to identifying human B1 cells and outline a carefully optimized approach that leads to uniform and reproducible data.